O impacto dos custos não-gerenciáveis na determinação das tarifas de energia elétrica: um estudo nas companhias distribuidoras do nordeste que tiveram revisão tarifária nos exercícios de 2003 e 2004 - Tavares, Adilson de Lima (2006)
This work presents results derived from a study related to impact on non-controllable costs in the determination of energy taxes. This is done analyzing tax review practiced by concessionaries responsible for the distribution of electrical energy located in the Northeastern Region of Brazil, between 2003 and 2004. This Region was chosen as a study area due to the researcher s expectation in congregating companies that deliver services to markets that have similar social-economical profiles. A brief explanation related to the restructuring of the electrical sector in Brazil is presented, pointing out that there was privatization of the great majority of these companies. The study also points out the definition of regulating rules in service delivery process. The components of taxes that are practiced by these companies aimed at final consumers, as well as the market as a whole and the revision process that is executed by Agência Nacional de Energia Elétrica ANEEL for the definition of these taxes are demonstrated in the research. A brief historical of the concessionaires that were focus of the research is presented, totaling five companies. Some data used by ANEEL in the tax review process was analyzed as well as data on components of approved taxes. It is concluded that as a media 47, 49% of the components of taxes in the researched companies correspond to the non-controllable costs. These is done considering previous classification by ANEEL in the tax review process. Although, if it is considered that these companies since 2006, by the means of participation in energy auctions are able to negotiate energy prices for their own needs, it is concluded that these concession contracts guarantee the delivery of the service to the costumer in the total tribute. The percentage of non-controllable costs is 16, 27% average of the tax. This means, amongst other information, that the government has a great deal of responsibility in the formation of price practiced by these companies and its target markets